The International Persistence and Resilience of Solitary Confinement - Reiter, Keramet (Oñati Socio-Legal Series, 2018)
Drawing on a combination of legal analysis and fieldwork conducted with prisoners and administrators in both Denmark and the United States, this article interrogates how solitary confinement has been defined and constrained - or not - in the context of U.S., European, and international law over time. Solitary confinement has existed consistently in prisons across the world, since the first prisons opened. Solitary has been surprisingly predictable over its long history: resilient to criticism, subject to ongoing debates about just how detrimental it is, and repeatedly producing instances of extreme and de-humanizing brutality. This consistency and predictability suggests substantial limitations inherent in the newest barrage of critiques leveled by courts, scholars, international human rights bodies, and professional associations against the practice of solitary confinement. Indeed, this reveals that many critiques of solitary confinement have failed because they have promoted reformist rather than non-reformist (or abolition) agendas - a distinction articulated by Mathiesen (1974/2014).